Analysis of Soil Replacement and Woven Geotextile Reinforcement on Embankment Stability - Agustina, Yani Putri; Handiman, Iman; Sarifah, Fitriana; Hamonangan, Efran Kemala; Irawan, Pengki; Gusnadi, Zakwan (INVOTEK: Jurnal Inovasi Vokasional dan Teknologi, 2024)
Toll roads are infrastructure built to improve the regional and national economy. The challenge faced on this toll road is soft soil as deep as 7 m. This research analyzes the stability of the embankment with a slope of 1V:2H and a height of 4.5 m without and with repair using the Limit Equilibrium Method (LEM) because the Safety Factor (SF) value in LEM provides a more critical value than the Finite Element Method (FEM). In addition, the settlement amount was also analyzed. The SF value in short term conditions with an embankment load of 1.31 < 1.4 and earthquake load of 0.83 < 1.1. Then, at pavement installation, 1.33 < 1.4, plus earthquake load 0.84 < 1.1. In long term conditions, during the operational period, 1.48 < 1.5, plus earthquake load 0.84 < 1.1. This indicates that the soil requires improvement. To address the problem, soil improvement utilized 2.5 m deep soil replacement and 75 kN woven geotextile. The SF value with repair under short term conditions, with embankment load 1.53 > 1.4, plus earthquake load 1.18 > 1.1. Then, at the time of pavement installation, 1.56 > 1.5, plus earthquake load 1.19 > 1.1. In the long term condition, it was 1.62 > 1.5 at the time of operation, plus earthquake load 1.22 > 1.1. The total settlement after the operation is 0.21 cm ? 10 cm and the settlement rate is 0.68 < 2 cm/year. This shows that improvements can increase the SF value and reduce settlement.